Lung ventilation and the physiology of breathing - Barrow, A; Pandit, J (Elsevier, 2014)
This article summarizes the anatomical features of the lungs, airway and thorax pertinent to the physiology of breathing and discusses chemoreceptor detection mechanisms, brainstem centres and relays involved in the control of breathing. We will discuss lung mechanics including spirometry, lung compliance, airway resistance and the role of surfactant and consider how these can be affected by disease states. It is recommended to revise principles of arterial blood gas analysis in addition to this article. © 2014 Elsevier Ltd. All rights reserved.